Answered

Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Which equation is equivalent to 2 - 2(3x - 1) = 2?
A.-6x = 2
B.-5x = 2
C.-6x + 4 = 2
D.-5x + 4 = 2


Sagot :

C would be the correct answer to this question.